Development of STEM-PjBL Based E-Modules on Acid-Base Material to Improve Learning Outcomes - Ginting, Al Miza; Amdayani, Susilawati (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2024)
This study aims to determine the needs analysis, validity, practicality, effectiveness and student response to STEM-PjBL-based E-Modules. This research was conducted at SMAS Kartika I-2 Medan and the sample of class XI IPA 2. The type of research used is Research and Development (R&D) and the development model is 4-D (Four D). The data collection technique is through interviews, observations, questionnaires and tests. Data analysis on the validity test uses the kappa moment formula and the effectiveness test uses the N-Gain test. The results obtained are analyzing the needs of teachers have not maximally used theÂ PjBLÂ learning model, and have never used STEM-PjBL-based E-Modules and the books used have not contained projects and STEM. As many as 69.7% of students feel bored and 57.6% of students prefer to do project-based learning. Validity obtained an average kappa moment of 0.82 very high category, from material experts 0.86 and media experts 0.79 very high category. Practicality by teachers obtained an average kappa moment of 0.99 very high category. Effectiveness obtained an average N-gain of 0.52 medium category. Student response obtained an average kappa moment of 0.81 very high category.